2019
DOI: 10.3390/en12020270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tailing-Edge Thickness on Aerodynamic Noise for Wind Turbine Airfoil

Abstract: The influence of wind turbine airfoil trailing edge thickness on aerodynamics and aerodynamic noise characteristics was studied using the computational fluid dynamics (CFD)/ Ffowcs Williams–Hawkings (FW–H) method in the present work. First, the airfoil of a DU97-W-300-flatback airfoil was chosen as the research object, and numerical method validation was performed. Three kinds of turbulence calculation methods (unsteady Reynolds average Navier-Stokes (URANS), detached eddy simulation (DES), and large eddy simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The detached eddy simulation (DES) method is a hybrid simulation method of Reynolds average Navier-Stokes (RANS)/large eddy simulation (LES) [41].…”
Section: Numerical Methods For Aero-noise Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The detached eddy simulation (DES) method is a hybrid simulation method of Reynolds average Navier-Stokes (RANS)/large eddy simulation (LES) [41].…”
Section: Numerical Methods For Aero-noise Calculationmentioning
confidence: 99%
“…The results showed that this method can be used to design vertical axis wind turbines with less noise and to determine the location of wind turbines with the least noise pollution. In 2019, Li et al [41] used computational fluid dynamics (CFD) and acoustic analogy to study the influence of the trailing edge thickness of a wind turbine airfoil on the aerodynamic noise of the airfoil. The results showed that the blunt trailing edge airfoil had a higher lift, but the aerodynamic noise of the trailing edge was also large.…”
Section: Introductionmentioning
confidence: 99%
“…A large eddy simulation (LES) is a spatial average of turbulent fluctuations, that is, large-scale vortices and small-scale vortices are separated using a filtering function [42]. More specifically, large-scale vortices are simulated directly, while small-scale vortices are closed using models.…”
Section: Large Eddy Simulationmentioning
confidence: 99%
“…In order to demonstrate mesh grid convergence, three sets of computational meshes with different densities were set up: 2,560,000 cells (coarse), 3,645,000 cells (medium), and 5,000,000 cells (fine). The three sets of computational results were obtained numerically, and the Richardson extrapolation method [41] was used to demonstrate convergence. Table 2 shows the results of the calculations and Richardson extrapolation.…”
Section: Numerical Conditionsmentioning
confidence: 99%